2017
DOI: 10.1111/ctr.12915
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic patterns and treatment of transplant glomerulopathy: A retrospective analysis

Abstract: Transplant glomerulopathy is mainly due to chronic antibody-mediated rejection and actually represents a major cause of long-term allograft failure. The lack of effective treatment remains a serious problem in transplantation. A retrospective and uni-center study was performed in 48 kidney allograft recipients with transplant glomerulopathy between January 2010 and December 2015. Median time for diagnosis was 7.1 (3.6-11.8) years post-transplant. Light microscopy showed severity of transplant glomerulopathy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…Very few studies take the percentage glomerulosclerosis into account in outcome prediction, likely because glomerulosclerosis is not included in the Banff classification and therefore remains under reported. We recently demonstrated a highly significant association between glomerulosclerosis, proteinuria, and graft outcome in univariate analysis, but glomerulosclerosis was not retained in multivariate models [43,47,65], which supports the concept that glomerulosclerosis is a secondary phenomenon and not an independent factor in graft outcome. More systematic inclusion of glomerulosclerosis in studies reporting on renal allograft histology, and in predictive models, seems necessary to elucidate the relevance of this lesion for prognostication (see below).…”
Section: Glomerulosclerosismentioning
confidence: 81%
“…Very few studies take the percentage glomerulosclerosis into account in outcome prediction, likely because glomerulosclerosis is not included in the Banff classification and therefore remains under reported. We recently demonstrated a highly significant association between glomerulosclerosis, proteinuria, and graft outcome in univariate analysis, but glomerulosclerosis was not retained in multivariate models [43,47,65], which supports the concept that glomerulosclerosis is a secondary phenomenon and not an independent factor in graft outcome. More systematic inclusion of glomerulosclerosis in studies reporting on renal allograft histology, and in predictive models, seems necessary to elucidate the relevance of this lesion for prognostication (see below).…”
Section: Glomerulosclerosismentioning
confidence: 81%
“…C4d+ in this study was found to be associated with inferior allograft survival only in univariate analysis. Abreu et al [26] demonstrated in a retrospective study that C4d+ TG cases were more likely to be treated with intravenous Ig and/or rituximab. Nevertheless, in this study, we observed that these treating modalities did not improve TG prognosis, which is compatible with a recently published study [27].…”
Section: Discussionmentioning
confidence: 99%
“…Abreau et al [5] demonstrated that PRA class II was associated with graft failure while Julie et al [25] and Layla et al [6] consistently showed that allograft survival/failure was independent of PRA levels. We failed to find PRA predictive of allograft survival in both univariate and multivariate analysis, which did not necessarily negate previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have analyzed the associations of variables at the time of biopsy with long-tern allograft outcome, therapeutic influences and pathologic factors that may also influence allograft survival were not accounted for in this study. However, recent studies have indicated that currently available treatment modalities for TG is ineffective to improve kidney allograft survival [5,30,31]. Additionally, patients included in this study are predominantly composed of forcause biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation